Studi in Silico Senyawa Metabolit Sekunder Daun Kenikir (Cosmos Caudatus Kunth.) Sebagai Antikanker Ovarium terhadap ESR-1 - Gabriel, Kevin; Hidayat, Nafisa Nurfatia; Khaerani, Fitri Azlia; Gaharani , Prodio Efa (Universitas Negeri Semarang, 2024)
Ovarian cancer is one of the diseases with a high mortality rate through estrogen receptor alpha (ESR1) as one of the causes of ovarian cancer. Current therapies for ovarian cancer can cause side effects and are expensive. Therefore, alternative therapies with fewer side effects and more affordable costs are needed. One of the herbs that is rich in flavonoid and phenolic acid content which has anticancer activity with its mechanism as a trigger for apoptosis in ovarian cancer cells is Kenikir leaf (Cosmos caudatus). The study was conducted through pharmacophore screening and molecular docking methods in silico with ESR-1 receptor (PDB code:1SJ0). In addition, absorption, distribution, and toxicity predictions were also carried out through the PreADMET page and the Lipinski Rule of Five suitability test. The results of this study concluded that luteolin is the most potential compound as an ESR-1 receptor inhibitor with a pharmacophore fit-score value of 51.36, binding energy of -8.43 kcal/mol, inhibition constant of 66.366x10-2 µM, and hydrogen bonds as ligand-receptor interactions.